Child Care and Women's Labor Force Participation in Romania - Fong, Monica; Lokshin, Michael (World Bank, Washington, DC, 2015)
The authors model the household demand for child care, the mother's participation in the labor force, and her working hours in Romania. Their model estimates the effects of the price of child care, the mother's wage, and household income on household behavior relating to child care and mothers working outside the home. They find that: Both the maternal decision to take a job and the decision to use out-of-home care are sensitive to the price of child care. A decrease in the price of child care can increase the number of mothers who work and thus reduce poverty in some households. The potential market wage of the mother has a significant positive effect on the decision to purchase market care and the decision to engage in paid employment. The level of household nonwage income has little effect on maternal employment and the demand for child care. In addition to facilitating women's work, kindergartens and creches appear to provide educational and social benefits for children. Close to half the children in these facilities have mothers who do not work. Further research is needed to assess the cost and nature of these benefits and to determine the appropriate roles for the private and public sectors in providing, financing, and regulating such services for working and nonworking mothers.